Liquid Biopsy-Driven Cetuximab Rechallenge Strategy in Molecularly Selected Metastatic Colorectal Cancer Patients - Mariani, Stefano; Puzzoni, Marco; Giampieri, Riccardo; Ziranu, Pina; Pusceddu, Valeria; Donisi, Clelia; Persano, Mara; Pinna, Giovanna; Cimbro, Erika; Parrino, Alissa; Spanu, Dario; Pretta, Andrea; et al. (Frontiers in Oncology, 2022)
Background Rechallenge with EGFR inhibitors represents a promising strategy for patients with RAS wild type (WT) colorectal cancer (CRC) but definitive selection criteria are lacking. Recently, the RAS WT status on circulating tumor DNA (ct-DNA) emerged as a potential watershed for this strategy. Our study explored the liquid biopsy-driven cetuximab rechallenge in a RAS and BRAF WT selected population. Methods CRC patients with RAS and BRAF WT both on tumor tissue and on ct-DNA at baseline receiving rechallenge with cetuximab were eligible for our analysis. Ct-DNA was analyzed for RAS-BRAF mutations with pyro-sequencing and nucleotide sequencing assays. Real-time PCR and droplet digital PCR were performed to confirm the RAS-BRAF mutational status. Results A total of 26 patients were included in our analysis. In the global population, RR was 25.0%, median overall survival (mOS) was 5.0 months, and median progression-free survival (mPFS) was 3.5 months. Previous response to anti-EGFR was associated with improved mPFS (5.0 vs. 2.0 months, HR: 0.26, p = 0.048); anti-EGFR free interval > 14 months and anti-EGFR free interval > 16 months were associated with improved mPFS (respectively 7.0 vs. 3.0 months, HR: 0.27, p = 0.013 and not reached vs. 3.0 months, HR: 0.20, p = 0.002) and with improved mOS (respectively 13.0 vs. 5.0 months, HR: 0.27, p = 0.013 and 13.0 vs. 5.0 months, HR: 0.20, p = 0.002). Previous lines >2 were correlated with improved mPFS (4.0 vs. 1.0 month, HR: 0.05, p = 0.041) and with improved mOS (7.0 vs. 1.0 month, HR: 0.045, p = 0.034). In a multiple logistic regression model, only the anti-EGFR free interval was confirmed to be a significant predictor for mOS and mPFS. Conclusions Liquid biopsy-driven cetuximab rechallenge was confirmed to be effective. The clinical outcome was consistent with available results from phase II studies. In addition to the molecular selection through the analysis of ct-DNA for RAS, the long anti-EGFR free interval is confirmed as a prospective selection criterion for this therapeutic option.